Environmental DNA for detecting Bulinus truncatus: A new environmental surveillance tool for schistosomiasis emergence risk assessment. Issue 2 (26th November 2019) - Mulero, Stephen; Boissier, Jérôme; Allienne, Jean‐François; Quilichini, Yann; Foata, Joséphine; Pointier, Jean‐Pierre; Rey, Olivier
Abstract: Under ongoing climate changes, the development of large‐scale monitoring tools for assessing the risk of disease emergence constitutes an urging challenge. This is particularly the case for snail‐borne diseases such as the urogenital bilharziasis that emerged in Corsica and threat European countries. The expansion of this tropical disease mainly relies on the local presence of competent snail hosts such as Bulinus truncatus . Unfortunately, very little is known about the actual repartition of freshwater snails worldwide which makes new emergences difficult to predict. In this study, we developed two ready‐to‐use environmental DNA‐based methods for assessing the distribution of B. truncatus from water samples collected in the field. We used two approaches, a quantitative PCR (qPCR) and a droplet digital PCR (ddPCR) approach. We successfully detected B. truncatus in natural environments where the snail was previously visually reported. Our environmental DNA diagnostic methods showed a high sensitivity (≈60 DNA copy per mL of filtered water) and a high specificity to B. truncatus . Results obtained in qPCR and ddPCR were very similar. This study demonstrates that environmental DNA diagnostics tools enable a sensitive large‐scale monitoring of snail‐borne diseases hence allowing the delimitation of areas potentially threatened by urogenital schistosomiasis. Abstract : Under ongoing climate changes, the development of large‐scale monitoring tools for assessing the risk of disease emergence constitutes an urging challenge. Especially for snail‐borne diseases such as the urogenital bilharziasis that threat European countries. The widespread of this tropical disease relies on the local presence of compatible snail hosts such as Bulinus truncatus, but very little is known about the actual repartition of this freshwater snail. In this study, we developed two ready‐to‐use environmental DNA‐based methods (using quantitative PCR and droplet digital PCR for the quick update of B. truncatus distribution from water samples collected in the field.